Keragaan Tegakan Merawan (Hopea mengarawan Miq.) dan Keruing Gunung (Dipterocarpus retusus Blume) di Hutan Penelitian Dramaga, Bogor - Cecep Kusmana; Arini Lathifah (Jurnal Silvikultur Tropika, 2021)
Merawan (H. mengarawan) and Keruing Gunung (Dipterocarpus retusus) are species of the Dipterocarpaceae family that exist in Dramaga Research Forest, Bogor. Merawan and Keruing Gunung have many benefits. The IUCN categorized merawan as critically endangered species, while Keruing Gunung included into Endangered. Therefore, these tree species are need to be cultivated and preserved. The purpose of this study is to examine existence and distribution of merawan and Keruing Gunung in Dramaga Research Forest, Bogor. The research method used was a combination of transect and line plot. The data analysis used includes vegetation analysis, soil analysis, and abiotic factors. The results showed that the composition of plant species has various results, which merawan and Keruing Gunung are the dominating species in the area. The growth curve of merawan and Keruing Gunung forms an inverted “J”, indicating the good regeneration of the species. The distribution patterns of merawan and Keruing Gunung had a clump distribution pattern, with Morishita index of 3,511 for merawan and 3,076 for Keruing Gunung. Keywords : distribution pattern, Morishita index, vegetation analysis, regeneration pattern